New Amphora and Halamphora (Bacillariophyta) species from springs in the northern Apennines (Emilia-Romagna, Italy) - Cantonati, Marco; Angeli, Nicola; Lange-Bertalot, Horst; Levkov, Zlatko (Botanical Garden Meise, 2019)
Background and aims – The detailed analysis of algae and cyanoprokaryotes in a heterogeneous group of spring habitats (including all the different typologies) of the northern Apennines (Emilia-Romagna Region, Italy) revealed a new Amphora species in a small mountain flowing spring with low conductivity, and a new Halamphora species in a large, inland-saline (Triassic gypsum), fast flowing spring (Poiano spring). The present study aims to describe in detail these two new species found in contrasting spring types. Methods – This study is based on light microscopy (both fresh –for plastids – and prepared materials) and scanning electron microscopy observations, as well as a thorough morphological, physical, chemical, and biological characterization of the habitats. Key results – Amphora eileencoxiae sp. nov. is most similar to A. vetula (and allied taxa), and is characterized by the outline with acutely rounded, moderately ventrally bent ends, by the dimensions, and by the well-defined, semi-elliptic dorsal area. Halamphora poianensis sp. nov. is most similar to H. gasseae but differs by the higher stria density, the clearly ventrally bent ends, and the strongly developed dorsal raphe ledge. Conclusions – This is a contribution to the knowledge of the genera Amphora and Halamphora in mountain springs in understudied geographic areas and inland-saline springs, the species communities of which are likely insufficiently explored.
Keywords: diatoms, springs, inland saline habitats, new species, Amphora eileencoxiae, Halamphora poianensis, northern Apennines